The Effects of Chromotherapy on the Stress Level of Patients with Hypertension - Hoda, Ferdinandus Suban; Mahoklory, Serly Sani (Universitas Muhammadiyah Surakarta, 2022)
Hypertension contributes to 7.5 million deaths or 12.8% of the total mortality rate globally, making it one of the major health problems and is the leading cause of death every year. The high mortality and morbidity rate of hypertension are related to depression and stress. Hence, preventive actions in reducing the stress levels and blood pressure are required. Chromotherapy is a non-pharmacological therapy option to lower blood pressure that has several advantages; inexpensive, easy implementation, and minimal side effects. This research aimed to determine the effectiveness of chromotherapy on the stress level of patients with hypertension. This is a pre-andpost- test quasi-experimental study involving 120 patients with hypertension. The chromotherapy effectively reduce stress level and blood pressure of the treatment group (p<0.05). Moreover, the mean score of stress level of treatment group was decreased to 40.10 (± 10.516), while the control group experienced the opposite; an increased mean score to 80.90 (± 12.288). Furthermore, the decreased blood pressure of treatment group was observed by 10-14 mmHg after chromotherapy treatment was given. The chromotherapy is a new innovation in complimentary therapy and can be used as an alternative non-pharmacological treatment that effectively reduces stress level and blood pressure.